Attentional Dissociation in Hypnosis And Neural Connectivity: Preliminary Evidence from Bilateral Electrodermal Activity. Issue 3 (2nd July 2016) - Bob, Petr; Siroka, Ivana
Abstract: According to recent findings, interhemispheric interactions and information connectivity represent crucial mechanisms used in processing information across various sensory modalities. To study these interactions, the authors measured bilateral electrodermal activity (EDA) in 33 psychiatric outpatients. The results show that, during congruent Stroop stimuli in hypnosis, the patients with higher hypnotizability manifest a decreased level of interhemispheric information transfer measured by pointwise transinformation (PTI) that was calculated from left and right EDA records. These results show that specific shifts of attentional focus during hypnosis are related to changes of interhemispheric interactions that may be reflected in neural connectivity calculated from the bilateral EDA measurement. This attentional shift may cause dissociated attentional control disturbing integrative functions of consciousness and contextual experiences.